2021
DOI: 10.22441/mix.2021.v11i3.004
|View full text |Cite
|
Sign up to set email alerts
|

Employee Performance Determinants, With Gender as a Group

Abstract: The purpose of this study is to analyze the influence of organizational commitment on employee performance; analyze the influence of organizational commitment on OCB; analyze the influence of OCB on employee performance; analyze the role of gender as the effect of moderation of organizational commitment on employee performance; analyze the role of gender as the effect of the moderating effect of organizational commitment on OCB, and analyze the role of gender as the effect of moderation on OCB on employee perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…It means that employees' organizational commitment does not affect their performance positively or negatively. This study supports previous research conducted by Sariani et al (2021), Indarti et al (2017), and Dewi et al (2021 that found no significant influence of Organizational Commitment on Employee Performance. Manifest variables that indicate the affective commitment dimension, M1.3, M1.1, and M1.2, respectively, have the highest outer loading values, indicating that affective commitment among employees is the most representative variable for organizational commitment.…”
Section: Discussionsupporting
confidence: 92%
“…It means that employees' organizational commitment does not affect their performance positively or negatively. This study supports previous research conducted by Sariani et al (2021), Indarti et al (2017), and Dewi et al (2021 that found no significant influence of Organizational Commitment on Employee Performance. Manifest variables that indicate the affective commitment dimension, M1.3, M1.1, and M1.2, respectively, have the highest outer loading values, indicating that affective commitment among employees is the most representative variable for organizational commitment.…”
Section: Discussionsupporting
confidence: 92%